Providing Education for Mothers with Stunting Toddlers through Healthy Toddler Class - Adinda Putri Sari Dewi; K Kusumastuti; Siti Mutoharoh; Wulan Rahmadani (Urecol Journal. Part F: Community Development, 2022)
Stunting is a state of malnutrition associated with insufficient nutrition so that it can be chronic. The purpose of this community service activity is to increase the knowledge of mothers with stunting toddlers. This activity was carried out in Selokerto Village, Sempor District, Kebumen Regency with 18 participants. The method used in this activity starts from the preparation stage, screening, giving mastery on stunting and complementary feeding, Tuina Massage and Evaluation. The activity assessment was carried out by analyzing the results of the pre-test and post-test questionnaires. The assessment from mothers with stunting toddlers is that most participants in the class for mothers with healthy toddlers experienced an increase in tests. This activity succeeded in increasing the knowledge of mothers with stunting toddlers in Selokerto Village, Sempor District, Kebumen Regency.